In operando XAS investigation of reduction and oxidation processes in cobalt and iron mixed spinels during the chemical loop reforming of ethanol. Issue 39 (26th September 2017) - Carraro, F.; Vozniuk, O.; Calvillo, L.; Nodari, L.; La Fontaine, C.; Cavani, F.; Agnoli, S.
Abstract : FeCo2 O4 and CoFe2 O4 nanoparticles have been studied as oxygen carriers for the chemical loop reforming of ethanol by using in operando X-ray absorption spectroscopy. Abstract : FeCo2 O4 and CoFe2 O4 nanoparticles have been studied as oxygen carriers for the Chemical Loop Reforming (CLR) of ethanol. By using in operando X-ray absorption spectroscopy we have followed in real time the chemical and structural changes that take place on the materials as a function of temperature and reactive atmosphere ( i.e. ethanol/water streams). During the first step of CLR for both oxides the most active chemical species are the cations in the tetrahedral sites, irrespective of their chemical nature. Quite rapidly the spinel structure is transformed into a mix of wüstite-type oxide and metal alloys, but the formation of a metal phase is easier in the case of cobalt, while iron shows a marked preference to form wüstite type oxide. Despite the good reducibility of FeCo2 O4 imparted by the high amount of cobalt, its performance in the production of hydrogen is quite poor due to an inefficient oxidation by water steam, which is able to oxidize only the outer shell of the nanoparticles. In contrast, CoFe2 O4 due to the residual presence of a reducible wüstite phase shows a higher hydrogen yield. Moreover, by combining the structural information provided by X-ray absorption spectroscopy with the analysis of the byproducts of ethanol decomposition we could infer that FeCo2 O4 is more selective than CoFe2 O4 for the selective dehydrogenation of ethanol to acetaldehyde because of the higher amount of Fe(iii ) ions in tetrahedral sites.